An investigation into stylistic devices in the autobiography “my life” by bill clinton - Nguyễn,Thị Thanh Thảo (ĐHĐN., 2015)
Though there have been many researches on stylistic devices, those used in writing autobiography, a distinguished type of writing, have not been deeply figured out. This thesis attempts to find out the stylistic devices in the autobiography “My Life” by Bill Clinton. By observation and investigation the research has found that metaphor, a powerful stylistic device to create images and parallelism, a structural stylistic device playing as the base for many other stylistic devices are widely used in volume I of the book. By using both qualitative and descriptive approach, the research has investigated the syntactic and pragmatic features of metaphor and parallelism in the book. The findings of the study have shown that metaphor and parallelism in the book were constructed from various types of syntactic structures and presented a number of pragmatic meaning. On the basis of the findings, some activities for teaching and learning English stylistic devices, especially learning metaphor and parallelism have been put forward. Finally, suggestions for further study are made for anyone that is interested in this problem to continue studying to perfect this research